Penerapan Algoritma Simple Additive Weighting untuk Membantu Dalam Menentukan Calon Penerima Bantuan Pangan Non Tunai - Andreas, Andri; Wiryadinata, Antonius; Agung, Halim (Institut Teknologi dan Bisnis Kalbis, 2019)
Bantuan Pangan Non Tunai (BPNT) is a program organized by the government in overcoming poverty and food needs. The BPNT program aims to reduce the burden of expenditure and provide more balanced nutrition to Beneficiary Families (KPM). However, in the implementation of the BPNT program there were still technical problems, including the determination of potential BPNT recipients who were wrongly targeted. To facilitate Government in determining prospective BPNT recipients, the authors make a decision support system using the Simple Additive Weighting method where this system generates ranking to choose citizens who are entitled to receive BPNT through calculating the criteria of each alternative. It is expected that this application can provide recommendations for prospective BPNT recipients who are more targeted.